Microwave activated voltammetry: The thermally enhanced anodic stripping detection of cadmium - Marken, F; Matthews, S; Compton, R; Coles, B (2000)
In situ microwave activation of electrochemical processes in a novel electrochemical cell, in which intense microwave radiation is focused locally into the region at the electrode surface-solution interface, is shown to allow high-temperature voltammetry experiments at 100 μm Pt disk electrodes. Factors such as the cell geometry and the deposition of a thin film of mercury are shown to influence the microwave effect. The detection of trace metals or impurities by anodic stripping voltammetry is a routinely applied procedure with applications especially in rapid online monitoring, in remote place analysis, or for extremely dilute samples. For cadmium detect on by anodic stripping voltammetry microwave radiation is demonstrated to strongly affect the accumulation process but not the stripping process. Calibration of the effects induced by microwave radiation on the experimentally observed voltammetric data, based on the equilibrium potentials for the Fe(CN)6/(4-/3-) and the Ru(NH3)6/(3+/2+) redox systems, demonstrates that the data obtained are consistent with a thermally enhanced process. The temperature achievable at the electrode-solution interface before boiling and cavitation occurs, is shown to be strongly dependent on the type of electrode material and surface morphology. At a mercury film electrode deposited on platinum temperatures in excess of 150°C can be applied in voltammetric experiments in a constant heating mode.